2022
DOI: 10.21203/rs.3.rs-1532981/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of COVID-19 Lockdowns on the development of educational, social and emotional gaps between the children - A Retrospective Chart Review

Abstract: Objective School closures due to the COVID-19 outbreak have affected the world's students physically, socially, and psychologically with an increase in the number of children and adolescent with anxiety, depression and drug abuse. Methods This study included 380 children evaluated in the outpatient Child Psychiatric Clinic, and were divided into two groups: before the lockdowns (BLD) (n = 248), from 1.2019 to 2.2020, and during the lockdowns (LD) (n = 132), from 3.2020 to 4.2021. Results When comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Quarantine due to the pandemic had a significant impact on young people. In their article, T. Ebert et al (2022) presented the results of a study of the impact of quarantine on Israeli students physically, socially and psychologically, how the number of children suffering from anxiety and depression has changed. It has been found that many children experienced learning, social, emotional, and behavioural gaps during the lockdown and lost the skills to cope with everyday challenges due to social isolation.…”
Section: IVmentioning
confidence: 99%
“…Quarantine due to the pandemic had a significant impact on young people. In their article, T. Ebert et al (2022) presented the results of a study of the impact of quarantine on Israeli students physically, socially and psychologically, how the number of children suffering from anxiety and depression has changed. It has been found that many children experienced learning, social, emotional, and behavioural gaps during the lockdown and lost the skills to cope with everyday challenges due to social isolation.…”
Section: IVmentioning
confidence: 99%
“…Quarantine due to the pandemic had a significant impact on young people. In their article, T. Ebert et al (2022) presented the results of a study of the impact of quarantine on Israeli students physically, socially and psychologically, how the number of children suffering from anxiety and depression has changed. It has been found that many children experienced learning, social, emotional, and behavioural gaps during the lockdown and lost the skills to cope with everyday challenges due to social isolation.…”
Section: IVmentioning
confidence: 99%